Induction of Genetic Variability by Colchicine Treatment in Stevia rebaudiana Bertoni. - A. Mahdi, Suhad; Mohan Meena, Chandra; Tholakabavi, Ashok (Al-Qadisiyah Journal of Pure Science, 2018)
In this study polyploidy was induced in Stevia rebaudiana Bertoni, (2n=22) by using different concentrations of colchicine (0.25%, 0.50%, 0.75%, 1.0%, 1.50%, and 2.5 %). Morphological measurements like plant height, leaf length, width and thickness, stomata number per unit area and number of inflorescences per plant were studied. Analysis of variance revealed highly significant differences among the plants. Flow cytometry analyses, identified the ploidy level. The results showed that the percentage of Stevioside content in leaves were (two and half times) higher than the tetraploid plants compared to control.